(untitled) (Altre Modernità, 2015)
In her work, Jeanette Winterson consistently shows an interest in history and the way in which it has been transmitted through generations. In particular, she attempts to fill in the gaps of historical representation by shedding light on those identities that were marginalised and made invisible because they ostensibly violated society’s norms, or because they were perceived as deviant and threatening for the social order. From her first novel Oranges Are Not the Only Fruit (1985) to her more recent works, Winterson reclaims a verbal and symbolic space for those subjects whom society has failed to recognise. Winterson narratively revisits history by adopting and combining several technical postmodern strategies, such as historiographic metafiction, parody, intertextuality, self-reflectivity and pastiche. In so doing, she aims to explore the cultural construction of sexual and gender identities as well as to challenge patriarchal and heterosexual hegemonic discourses.